2012
DOI: 10.1080/01457632.2012.692296
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Air-Side Performance of a Multipass Parallel and Counter Cross-Flow L-Footed Spiral Fin-and-Tube Heat Exchanger

Abstract: This study conducted experiments on the air-side performance of novel L-footed spiral fin-and-tube heat exchangers that were faced with airflow at high Reynolds numbers 000). The examined heat exchangers have a multipass paralleland-counter cross-flow type of water flow arrangement. This flow arrangement is a combination of the parallel cross-flow and the counter cross-flow. This type of water flow arrangement may be the best fit for the reverse-flow system, because it can provide constant heat-exchange effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…The correlations for the Colburn factor and the friction factor were presented in the study. In the similar study on the same experimental setup Pongsoi et al (2012a) studied the effect of number of tube rows along with the variation in the fin height. The effect of the number of tube rows was similar as were found in the previous study.…”
Section: Side Viewmentioning
confidence: 98%
“…The correlations for the Colburn factor and the friction factor were presented in the study. In the similar study on the same experimental setup Pongsoi et al (2012a) studied the effect of number of tube rows along with the variation in the fin height. The effect of the number of tube rows was similar as were found in the previous study.…”
Section: Side Viewmentioning
confidence: 98%
“…Further details about the data reduction can be seen from Pongsoi et al [11][12][13][14][15][16]. The efficiency of a radial fin with rectangular profile is based on the derivation of Gardner [20], i.e.,…”
Section: Data Reductionmentioning
confidence: 99%
“…In this study, the serrated welded spiral fin-and-tube heat exchangers having Z-shape tube arrangements and the 2 tube rows are investigated by using the experimental apparatus of Pongsoi et al [11][12][13][14][15] and Pongsoi and Wongwises [16], including the water flow loop, air-flow supply, measuring instruments, and data acquisition. The detailed geometrical parameters of the test sections are shown according to Table 1.…”
Section: Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The experiments on heat exchanger with annular fins of various fins spacings and different air speeds under the free and forced convection were conducted by Han-Taw Chen et al, [3][4][5][6] and they reported that the value of heat transfer coefficient increases and efficiency decreased with increase in fin spacing and air speed values. Parinya pangs et al 7 conducted the experiments on the air-side performance of novel L footed spiral fin and tube heat exchangers. They concluded that the number of tube rows had no significant effect on the air side heat transfer and the pressure drop increases as the fin outside diameter increased for the same number of tube rows.…”
mentioning
confidence: 99%